Lantbrukarens inställning till skuldsättning och val av kreditinstitut - Högberg, Gustaf (2010)

(untitled)
The agricultural sector is characterized by larger crop farms and more extensive livestock production. The efficiency improvement is partly a result from a stronger competition in the global market. The agricultural products need to be produced at a lower cost than competitors in order to survive as a farmer. The solution is larger firms that benefit from economies of scale. This brings large investments that create a greater need for leverage and closer relation to the credit agency. What influences the farmers’ decision to increase leverage and enact one comprehensive investment plan? Those who choose to make the investment are dedicated to develop their business.